Rudy Van Gelder in Hackensack: Defining the Jazz Sound in the 1950s - Skea, Dan (Current Musicology, 2001)
To many jazz aficionados, the name Rudy Van Gelder is virtually syn-onymous with jazz recording. Still active today, this reclusive self-taught craftsman is by far the most prolific and accomplished sound engineer in the history of jazz, recording many of the music's most acclaimed albums. In a career that has now spanned half a century and has paralleled devel-opments in both modern jazz and recording technology, Van Gelder has contributed to advances in both areas, simultaneously shaping and being shaped by these new developments.